Analysis of Accountability and Transparency in Financial Management in the Islamic Perspective of Central Buton Regency - Agustyawati, Dwi (International Journal of Management Progress, 2022)
This study aims to analyze the accountability and transparency of financial management in Langkomu Village, Mawasangka Tengah District, Central Buton Regency based on Permendagri No. 1.113 of 2014. Field research, library research, and interviews were used as data collection methods. The data analysis method used by the author is descriptive and qualitative.Based on the results of the analysis and discussion of the data, it can be concluded that (1) The responsibilities for the village financial management planning stage in Langkomu village in its implementation have been allocated and are guided by Permendagri No. 113 of 2014. This is evidenced by the existence of Raperbedes APBDesa which was discussed between the village government and the Village Consultative Body (BPD) in the village deliberation forum. (2) Transparency of village financial management in Langkamu Village in its implementation is in accordance with Permendagri No. 113 of 2014, every village has a bulletin board or billboard and village accountability reports are reported to the Regent/Mayor through the Camat. (3) At the reporting and accountability stages of the APBDes Implementation Report, Langkomu Village uses the implementation report format and is guided by Permendagri No. 113 of 2014, namely village reports on the implementation of the first and second semesters, as well as reporting reports on the implementation of the APBDesa implementation at the end of the fiscal year.